Exploring critical literacy of elementary school teacher education students through semantic studies - Kharisma, Nanda Veruna Enun; Jannah, Yunita Miftahul (Privietlab, 2025)
Developing critical literacy is crucial for elementary school teacher education students to understand texts beyond their literal meanings. This study aimed to describe students' critical literacy skills in interpreting texts from a semantic perspective. Using a descriptive qualitative approach, data were collected from text analysis assignments and class presentations of 30 students and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that students performed well in identifying denotative meanings, demonstrated moderate ability in interpreting connotative meanings and synonymy/antonymy relationships, but struggled with hyponymy/polysemy relationships and ideological or contextual reflection. These results suggest that students are more adept at understanding literal meanings than at interpreting implicit or contextual meanings. This study highlights the importance of explicitly integrating semantic studies into teacher education programs to strengthen prospective teachers' critical literacy, particularly in analyzing complex meaning relationships and the ideological dimensions of texts.